2014
DOI: 10.1021/ef500648k
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Reduction of CO2 in Aqueous Solution on Surface-Fluorinated Anatase TiO2 Nanosheets with Exposed {001} Facets

Abstract: Photocatalytic reduction of carbon dioxide can activate chemically inert carbon dioxide by the use of renewable energy. In the present work, the main products of photocatalytic reduction of CO 2 in aqueous TiO 2 suspensions were found to be methane, methanol, formaldehyde, carbon monoxide, and H 2 . Anatase TiO 2 catalysts with various morphologies, such as nanoparticle, nanotube, and nanosheet, were synthesized through a hydrothermal method. The TiO 2 nanosheets were more active than the nanotubes or nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 77 publications
1
68
0
5
Order By: Relevance
“…160 The TNTs calcined at 400°C yielded 0.50 μmol g −1 h −1 of methane, whereas TNRs produced only 0.33 μmol g −1 h −1 ; the authors attributed this difference to the greater surface polarity and acidity present on the inner He et al and generated CO, formaldehyde, methanol, and methane in basic solution. 145 The quantum efficiencies of these TNTs were about the same as those of the nanoparticles, on a surface area basis. Wang et al modified anatase TNRs with rutile NPs and found an increase in activity from 1.29 to 2.36 μmol g −1 h −1 of methane under UV light.…”
Section: •−mentioning
confidence: 85%
See 2 more Smart Citations
“…160 The TNTs calcined at 400°C yielded 0.50 μmol g −1 h −1 of methane, whereas TNRs produced only 0.33 μmol g −1 h −1 ; the authors attributed this difference to the greater surface polarity and acidity present on the inner He et al and generated CO, formaldehyde, methanol, and methane in basic solution. 145 The quantum efficiencies of these TNTs were about the same as those of the nanoparticles, on a surface area basis. Wang et al modified anatase TNRs with rutile NPs and found an increase in activity from 1.29 to 2.36 μmol g −1 h −1 of methane under UV light.…”
Section: •−mentioning
confidence: 85%
“…Doping of TiO 2 with other elements has been employed to alter the band gap and increase catalytic activity for CO 2 reduction. These dopants, which include nitrogen, 140,143,144 fluorine, 145 iodine, 141 cerium, 142 and rhodium, 146 were incorporated into the structure of TiO 2 .…”
Section: Metallic Co-catalysts On Tiomentioning
confidence: 99%
See 1 more Smart Citation
“…It is known, however, that the TiO 6 octahedra share edges and corners in rutile but only edges in anatase, and the probability of the latter can be much higher. 22,69,70 It is known that urea homogeneous precipitation is a common method to prepare monodisperse spherical particles. For the above reasons, anatase rather than rutile nanoparticles are directly crystallized in this study.…”
Section: Formation Mechanism Of the Foamed Crystallites And Factors Amentioning
confidence: 99%
“…Since then, studies on (001) faceted anatase TiO 2 have been completed [20][21][22][23][24][25][26][27]. However, most of the (001) faceted anatase TiO 2 crystals were prepared at high temperature through calcination or hydrothermal techniques [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%